(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
This article examines the presence of Early Maladaptive Schemas presented by Lourenço Mutarelli´s character according to Jeffrey Young. Young developed the Schema Theory categorizing five domains corresponding to each cognitive schema: Disconnection and Rejection, Impaired Autonomy and Performance, Impaired Limits, Other-Directedness and Over Vigilance and Inhibition. The cognitive schemas were identified and analyzed over the Lourenço Mutarelli´s material who created an autobiographical character in his blog, his interviews on the internet, in his comic books and novels. The domains that have prevailed within the material analyzed were: Disconnection and Rejection, Impaired Autonomy and Performance, and OverVigilance and Inhibition.